PENGARUH MEDIA AUDIOVISUAL DENGAN MENGGUNAKAN WONDERSHARE FILMORA DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK CERITA SISWA KELAS VIII SMP NEGERI 2 BAUBAU - Yusnan, Muh (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of this study is to see if Wondershare Filmora has a substantial impact on developing story listening abilities in Class VIII students at SMP Negeri 2 Baubau. Students in classes VIIIa and VIIIb at SMP Negeri 2 Baubau, a total of 40 students, were the subjects of this study. The results of this study indicate that (1) there is a significant effect of using audiovisual media on the effectiveness of learning students' story listening skills. This is indicated by the value of tcount which is greater than ttable (12,353>2,042), with a significance value of 0.000 which is smaller than a significance of 0.05 (0.000<0.05); and (2) there is a difference in the effect of audiovisual media in learning students' story listening skills compared to using conventional methods, which is shown from the results of the average score on the posttest being greater than the pretest (17.65>14.65). The magnitude of the increase in the level of story listening skills of students who are taught using conventional methods and the level of students' story listening skills taught using audiovisual media is 3.00.